The morphological and biochemical blood parameters of sheep affected by mastitis - Kereyev, A. K.; Sengaliyev, Y. M.; Gabdullin, D. E. (Жәңгір хан атындағы БҚАТУ, 2024)
Mastitis in sheep causes significant harm both to animal health and to the sheep farming economy. Treatment and prevention of mastitis require substantial investment in acquiring medicinal products, antiseptics, veterinary services, and other necessary materials. Morphological and biochemical blood parameters can serve as important indicators for diagnosing mastitis in sheep. The article presents the results of a study on the morphological and biochemical blood parameters of sheep affected by various forms of mastitis. The investigation of morphological and biochemical blood parameters in acute catarrhal, serous, and subclinical forms of mastitis in sheep revealed characteristic changes in blood before and after treatment. In cases of acute catarrhal, serous, and subclinical mastitis, a decrease in the number of erythrocytes and hemoglobin levels, an increase in leukocyte count, a decrease in glucose levels, an increase in total protein, and a decrease in albumin levels were observed. For treatment, Kalankhin preparation was used, which was rubbed into the udder. Additionally, the intracisternal administration of a physiologic saline solution, preheated to 37°C, at a dose of 20 ml with a concentration of 600 mg/L, was performed for three days. After treatment, blood parameters returned to physiological norms, where an increase in the number of erythrocytes and hemoglobin levels, a decrease in leukocyte count, an increase in glucose levels, a decrease in total protein, and an increase in albumin levels were observed. These changes indicate the restoration of metabolism, a reduction in the inflammatory process, and an improvement in metabolic exchange after treatment. Thus, the conducted study showed that acute catarrhal, serous, and subclinical forms of mastitis in sheep lead to shifts in morphological and biochemical blood parameters. After treatment, changes in parameters indicate a positive trend in restoring homeostasis and animal health. The use of environmentally friendly and safe preparations helps increase the effectiveness of treatment and the organism's resistance to diseases.
Ғылым және білім: Ғылым, зерттеулер, білім: даму тенденциялары: акад. Қ. И. Сәтбаевтың 125 жылдығына арналған халықаралық ғылыми-практ. конф. материалдар жинағы (12 сәуір 2024 ж.) = Наука и образование: Наука, исследования, образование: тенденции развития: сб. мат. междунар. науч.-практ. конф. посвящ. 125-летию акад. К. И. Сатпаева (12 апреля 2024 г.) = Science and education: Science, research, education: development trends: unternational scientific and practical conf. dedicated to the 125th anniversary of acad. K. I. Satpayev (12 april 2024). - Орал: Жәңгір хан атындағы БҚАТУ. - 2024. - № 2 (75) : қосымша № 1. - Р. 151-158
Keywords: mastitis; ғылыми журнал; blood; sheep; biochemistry; erythrocytes; leukocytes; мастит; мастит овец; эритроциты; лейкоциты; конференции